2013
DOI: 10.1371/journal.pone.0083671
|View full text |Cite
|
Sign up to set email alerts
|

Bottlenecks of Motion Processing during a Visual Glance: The Leaky Flask Model

Abstract: Where do the bottlenecks for information and attention lie when our visual system processes incoming stimuli? The human visual system encodes the incoming stimulus and transfers its contents into three major memory systems with increasing time scales, viz., sensory (or iconic) memory, visual short-term memory (VSTM), and long-term memory (LTM). It is commonly believed that the major bottleneck of information processing resides in VSTM. In contrast to this view, we show major bottlenecks for motion processing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(57 citation statements)
references
References 68 publications
3
54
0
Order By: Relevance
“…2 (the first column). In agreement with previous studies (Huyhn et al, 2015;Ogmen et al, 2013), we found a main effect of set size for six of seven observers. In fact, the observer for which set size was not present in the best model (SOA and set size interaction alone was sufficient to fit data), was SA who is one of the authors and extremely trained on orientation judgment tasks.…”
Section: Implications For Models Of Attentionsupporting
confidence: 93%
See 2 more Smart Citations
“…2 (the first column). In agreement with previous studies (Huyhn et al, 2015;Ogmen et al, 2013), we found a main effect of set size for six of seven observers. In fact, the observer for which set size was not present in the best model (SOA and set size interaction alone was sufficient to fit data), was SA who is one of the authors and extremely trained on orientation judgment tasks.…”
Section: Implications For Models Of Attentionsupporting
confidence: 93%
“…We obtained masking functions after transforming response errors to a probability-like measure such that performance values of 0.5 and 1 correspond to chance and perfect performance, respectively. We calculated transformed performance (Ogmen et al, 2013) as:…”
Section: Stimuli and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possibility is transformation of information into other representational formats, such as linguistic format (e.g., for describing tastes, musical sounds, etc.). It is likely that much of the information in the perceived present is lost without entering further stores or processing, because of processing bottlenecks (Jacob et al, 2013;Öğmen, Ekiz, Huynh, Bedell, & Tripathy, 2013;Sperling, 1960) or interference from subsequent information input. Greene (2016) commented that the results of a study by Keysers, Xiao, Földiák, and Perrett (2001) suggested that "the information provided by a brief display can be compartmentalized and buffered against interference from information that follows as soon as 14 ms later" (p. 222).…”
Section: Perceptual Processes and Productsmentioning
confidence: 99%
“…That would certainly be an advantage. Information is likely to be lost before it exits from perceptual processing, partly because of the need for attentive Discrete temporal frames 74 maintenance (Rensink, 2000) and partly because of the increasingly limited capacity of postperceptual stores (Jacob et al, 2013;Öğmen et al, 2013;Sligte et al, 2010;Sperling, 1960).…”
Section: 6: What Would Frames Do For Us?mentioning
confidence: 99%